2021
DOI: 10.1016/j.jsmc.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Measurements in Women

Abstract: Both objective and subjective measures of sleep and sleep-related variables seem to show differences between women and men. Most methods and instruments assessing sleep have not been substantially tested for sex or gender differences, and only few studies had the primary aim to investigate sex or gender differences. There are to date no guidelines as to whether or not the set up or scoring of sleep studies should be performed differently in women and men. Future studies need to be specifically designed to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 142 publications
1
2
0
Order By: Relevance
“…Women also more often obtained results indicating borderline insomnia, both in rural (24.9%) and urban (18.14%) areas. Other authors have reported similar results, showing a greater incidence of insomnia in women [3,5,32,33,34].…”
Section: Discussionsupporting
confidence: 66%
“…Women also more often obtained results indicating borderline insomnia, both in rural (24.9%) and urban (18.14%) areas. Other authors have reported similar results, showing a greater incidence of insomnia in women [3,5,32,33,34].…”
Section: Discussionsupporting
confidence: 66%
“…We did not assess tau deposition within the brain, considering that tau metabolism is also sleep related 42 and more directly related to cognitive disturbances in older individuals 49 . Finally, although sex difference has been described previously in sleep literature 50 and in pathophysiology of AD, 47 in the actigraphy/amyloid literature, possible sex interactions have not been clearly investigated yet. Thus there is a need for additional studies on this field directly addressing the sex difference.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate logistic regression analyses showed that females, new rural cooperative medical insurance, depression, and anxiety were independent risk factors for sleep disorders in individuals with CHD ( P < 0.05). According to research by Ulander et al [ 11 ], women are more prone than men to experience sleep disorders. According to Wang et al [ 12 ], female cancer patients have an increased incidence of sleep disorders.…”
Section: Discussionmentioning
confidence: 99%